2019
DOI: 10.1186/s12866-019-1641-1
|View full text |Cite
|
Sign up to set email alerts
|

A new culture-based method for rapid identification of microorganisms in polymicrobial blood cultures by MALDI-TOF MS

Abstract: BackgroundThe application of matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry (MS) to microbial identification has allowed the development of rapid methods for identification of microorganisms directly in positive, blood cultures (BCs). These methods can yield accurate results for monomicrobial BCs, but often fail to identify multiple microorganisms in polymicrobial BCs. The present study was aimed at establishing a rapid and simple method for identification of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The results of this study were consistent with that of other recent studies denoting the efficacy and efficiency of MALDI-TOF MS for the identification of Gram-negative bacteria [ 13 , 33 , 34 ]. Moreover, this study indicated that a replacement for the traditional identification method for R. ornithinolytica isolation in the microbiology laboratory was important.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study were consistent with that of other recent studies denoting the efficacy and efficiency of MALDI-TOF MS for the identification of Gram-negative bacteria [ 13 , 33 , 34 ]. Moreover, this study indicated that a replacement for the traditional identification method for R. ornithinolytica isolation in the microbiology laboratory was important.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that the M1 method, which eliminated the incubation of blood samples in liquid medium, saved approximately 35 to 43 h compared to the time required for the standard blood culture method. Though MALDI-TOF MS identification directly with positive blood culture has been used more widely in recent years, it is still difficult to analyze positive blood culture with polymicrobial infection (36). Therefore, in this retrospective study, the standard blood culture method still included the time for individual colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…The short incubation method has been used for polymicrobial cases as well. Although there is a report indicating that both microorganisms present in 43 (86%) of 50 polymicrobial blood culture bottles were correctly identified after short-term culture [60], it is a general view that short incubation method is not successfully applicable to polymicrobial blood stream infections [19].…”
Section: Id Of Polymicrobial Cultures With Maldi-tof Msmentioning
confidence: 97%